2003
DOI: 10.1097/01.sla.0000098617.21801.95
|View full text |Cite
|
Sign up to set email alerts
|

The Need for a Prophylactic Gastrojejunostomy for Unresectable Periampullary Cancer

Abstract: Prophylactic gastrojejunostomy significantly decreases the incidence of gastric outlet obstruction without increasing complication rates. There were no differences in quality of life between the two groups. Together with the previous randomized trial from the Hopkins group, this study provides sufficient evidence to state that a double bypass consisting of a hepaticojejunostomy and a prophylactic gastrojejunostomy is preferable to a single bypass consisting of only a hepaticojejunostomy in patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(41 citation statements)
references
References 48 publications
(47 reference statements)
2
36
0
3
Order By: Relevance
“…A randomized trial performed in the Academic Medical Center between 1999 and 2002 shows comparable results [21]. In this study, 21% of the patients needed reoperation after hepaticojejunostomy because of late gastrointestinal obstruction.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…A randomized trial performed in the Academic Medical Center between 1999 and 2002 shows comparable results [21]. In this study, 21% of the patients needed reoperation after hepaticojejunostomy because of late gastrointestinal obstruction.…”
Section: Discussionsupporting
confidence: 52%
“…Distant metastases were defined as histologically proven metastases in the liver or in lymph nodes outside the resection specimen (N3). A few patients only received a hepaticojejunostomy as part of a prospective trial [21]. Cholecystectomy and chemical splanchnicectomy with 50% ethanol were routinely performed.…”
Section: Methodsmentioning
confidence: 99%
“…Other investigators have reported similar difficulties. A randomized trial29 examining QoL in patients with unresectable periampullary tumours with or without prophylactic gastrojejunostomy reported a compliance rate of 90 per cent in the first 4 months of follow‐up, but it decreased to 75 per cent in the final 2 months of the study. Likewise, another randomized trial30 comparing stenting with surgical bypass for malignant gastric outlet obstruction reported a compliance rate of 57 per cent with follow‐up surveys at 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…In the AMC every patient with locally advanced disease underwent a double bypass in a trial setting [28, 29]. In the EMC only patients with signs of obstruction peri- and postoperatively underwent a bypass.…”
Section: Discussionmentioning
confidence: 99%